ปัจจัยที่มีผลต่อพฤติกรรมการป้องกันความเสี่ยงด้านสุขภาพจากการทำงานของพนักงาน ห้องปฏิบัติการทางการแพทย์ โรงพยาบาลระดับตติยภูมิ เขตภาคเหนือตอนล่าง - คันธสร วณิชชา; สงทับ อาจินต์ (Journal of Medicine and Health Sciences, 2018)
บทคัดย่อ การวิจัยแบบภาคตัดขวางเพื่อศึกษาพฤติกรรมการป้องกันความเสี่ยงด้านสุขภาพจากการทางานและปัจจัยที่มีผลต่อพฤติกรรมการป้องกันความเสี่ยงด้านสุขภาพจากการทำงานของพนักงานห้องปฏิบัติการ ทางการแพทย์ โรงพยาบาลระดับตติยภูมิ เขต 2 และเขต 3 สังกัดกระทรวงสาธารณสุข ในเขตภาคเหนือตอนล่าง กลุ่มตัวอย่างจำนวน 202 คน คัดเลือกโดยวิธีการสุ่มแบ่งกลุ่ม (Stratified cluster sampling) เก็บข้อมูลด้วย แบบสอบถาม วิเคราะห์ข้อมูลด้วยความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติถดถอยพหุคูณ ผลการศึกษาวิจัย พบว่ากลุ่มตัวอย่างส่วนใหญ่เป็นเพศหญิง ร้อยละ 66.3 อายุเฉลี่ย 41.46 ปี สถานภาพสมรสคู่ ร้อยละ 53.0 จบการศึกษาระดับปริญญาตรีขึ้นไป ร้อยละ 68.8 รายได้เฉลี่ยต่อเดือน 26,075 บาท เป็น นักเทคนิคการแพทย์ ร้อยละ 47.0 ประสบการณ์การทำงานในแผนกงานที่ปฏิบัติมากกว่า 20 ปีขึ้นไป ร้อยละ 39.1 มีการทำงานหมุนเวียนเป็นกะเช้า/บ่าย/ดึก ร้อยละ 75.2 เคยประสบอุบัติเหตุในการทำงาน ร้อยละ 51.5 การสัมผัสสิ่งคุกคามสุขภาพโดยรวมอยู่ในระดับปานกลาง (Mean = 2.45, SD = 0.46) โดยพบว่าสัมผัสกับ สิ่งคุกคามสุขภาพทางชีวภาพมากที่สุด คือ การสัมผัส เลือด สารคัดหลั่งและเนื้อเยื่อ ร้อยละ 59.9 สัมผัสมาก กับเชื้อกลุ่มเสี่ยงที่ 2 ที่สร้างความเสี่ยงต่อการเจ็บป่วยปานกลางแก่ผู้สัมผัส ร้อยละ 52.5 การรับรู้ความเสี่ยง Abstract This cross-sectional study was conducted to determine the preventive health risk behaviors and factors affecting preventive health risk behaviors among medical laboratory workers at tertiary hospitals in the area of 2nd and 3rd Health Regions under the authority of the Ministry of Public Health, located in lower northern Thailand. A total of 202 samples were recruited, using stratified cluster sampling and a questionnaire was employed for data ollection. The data was analyzed by frequency, percentage, standard division and multiple regression analysis. The results revealed that most of the samples were 66.30% female with a mean age of 41.46 years. Fifty three percent were married and 68.8% completed Bachelor’s degree or higher. Their monthly incomes were 26,075 baht. Forty-seven percent of them were medical technicians of 39.1% had working over 20 years. Approximately 75.0% had a rotation in their shift morning or afternoon and late and 51.5% had an accident at work. In overview, the samples exposed health threats at moderate level (Mean = 2.45, SD = 0.46), and the perceived risk and they had supported policy in term of safety from the agency was observed at high level (Mean = 3.83, SD = 0.05) and (Mean = 1.47, SD = 0.25). However, the preventive health risk behaviours were at moderate levels (Mean = 3.37, SD = 0.43). The factors that affected preventive health risk behaviours were ordered by the variances of preventive health risk behaviours presented from maximum to minimum. These included 1) exposure to health threats from work 2) perceived benefits of the preventive health risk behaviours practices and 3) ages. These factors could predict preventive health risk behaviours at 21.7%, at a statistically significant level of 0.05.